OPTIMIZING TAX REPORTING PROCESSES DURING COMPANY LIQUIDATION - ⁠ Armine Pavleian (Modern American Journals, 2025)
This article examines taxation and tax reporting problem areas that arise during company liquidation and proposes practical approaches to optimizing these processes. Based on an analysis of scientific literature, key risks are identified and recommendations are developed for preliminary tax planning, digitalization of reporting, the use of checklists, and final reconciliation procedures with the tax authorities.
Keywords: Company liquidation, tax reporting, tax planning, process optimization, digitalization, tax reconciliation.